Combined radiation therapy and surgery in the treatment of esophageal cancer - Praderi, Luis A; Parada, Ricardo (Cirugía del Uruguay, 1975)
The authors suggest a eombined treatmcnt of preoperative irradiation and surgical excision for patients with careinoma of tbe esophagus. Wlth cobalt-60 gammo. rays thy give a dose of 4000 rads jn 3 weeks, in a large fieId, 8 cm wide and 15 cm or more high, centered by the lesiono They do not carry out a total irradiation oí the esophagus, nOr oí tbe celiac regian. 2 wceks aíter discontinuing radiotherapy, they perform the eso· phagectorny with proximal gastrectomy and celiae Iymph nodes excision by a single left thoraeic approach for juxtufreoie tumors, and by a combined approaCh, abdo· minal and right thoracie, for the tumors of the ntlddlc third or the uppcr ones of the lower third. In all cases continulty was restored by intrathoracic esophago-gastrostomy. Out oi. the 18 p;\tients thus treated 16 were res~cted (88 % ). Operative mortality was 25 % In thereseeted patients (4 in 16). 3 oí them due to disrup!ion of the anastomosis. 5 patients have survived (average 26.4 months) , and 6 oí them have d ied (average, 15 monlhs after su.rgery) . Global survivnl of the serie!; up 10 ' he moment has been 20 months.